Global Initiatives for Higher Education Development - Goretti , Sr. Kaahwa Maria (African Journal of Education,Science and Technology (AJEST), 2017)
Higher Education and globalization are connected and inseparable in many ways. Higher Education is a key factor in a nation’s effort to develop a highly skilled workforce for competing in the global economy. Globalization is an integration of economies, societies, knowledge and cultures into a borderless worldwide communications systems and supply network. Globalization in relation to higher education has broken barriers and is connecting Institutions across the world. The global has made universities visible, facilitating knowledge flows, values on global learning, and creating new opportunities for advanced learning. Higher education has a critical responsibility for training a country’s professional personnel. This research explored how Higher Education improves economies and how globalization has impacted on Higher Education. The study dealt with student and teacher mobility; Curriculum reform and reviews; the opportunities which come with globalization; the challenges of higher education and globalization; Quality in Higher Education; Network of teaching and learning in globalization; and Universities in globalized world. The study concluded that globalization has come to stay and it has both positive and negative effects. The study recommends that High Education should not be influenced in the quality of its programmes by globalization; Higher Education should go curriculum reforms and innovations to meet the changing needs; High Education should exploit the staff and student mobility; and Higher Education should harmonize systems in Education across-boarders to exploit more opportunities.